Стадії створення юридичної особи - Шишка, Р.; Shyshka, R. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
В статті розглядаються теоретичні та практичні аспекти створення юридичної особи, надалі розвинута та уточнена раніше висунута автором концепція стадій створення юридичної особи та зміст кожної із них. Виділено ініціативну, організаційну та легалізаційну стадій створення юридичної особи. З моменту внесення юридичної особи до Єдиного державного реєстру юридичних осіб та фізичних осіб-підприємців юридична особа є створеною. Це одночасно означає можливість отримати відкриту інформацію про юридичні особу та її життєвий цикл, з моменту отримання Свідоцтва про державну реєстрацію виникає її право- та дієздатність. Запропоновано зміни та доповнення до ст. 87 ЦК України та подальша дискусія по зазначеним проблемам.The article deals with the theoretical and practical aspects of the legal entity, further developed and refined previously nominated author’s conception of stages of the creation of legal entity and the content of each of them. The initiative, organizational stages and the stage of legalization of a legal entity are highlighted. Since the moment of entry the legal entity to The United state register of legal entities and entrepreneurs the entity is created. It also means the opportunity to get the public information about legal entities, from the receipt the certificate of state registration arises its legal capacity and capability. The amendments to the Art. 87 of the Civil Code of Ukraine are proposed, in particular, the author formulated the rule that creating a legal entity its founder or founders justify the creation and conduct their own expense all necessary actions and coordination, develop, and in accordance with the law take constituent documents that are signed by the founder or an authorized representative of the founder, unless the law establishes a different procedure for its creation, unless the law establishes a different procedure for its creation. For the registration of the legal entity its founder/founders or their representative have to submit to the registration authority notarized copies of constituent documents and other documents prescribed by the law.
Stages of the Creating the Legal Entity
Keywords: юридична особа; правосуб’єктність; державна реєстрація; статутні документи; цивільне право; legal entity; legal personality; state registration; statutory documents; civil law